ESTIMATION OF GABAPENTIN IN HUMAN PLASMA USING LC-MS/MS METHOD - BINAYA, DAS (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: The objective of this research was to develop and validate a simple, sensitive and specific Liquid Chromatographyâ€“Tandem Mass Spectrometry (LCâ€“MS/MS) quantification of Gabapentin in human plasma. The analytical method consists of liquid-liquid extraction of plasma sample followed by the determination of Gabapentin by a LCâ€“MS/MS. Method: The analyte was separated on a Zorbax Eclipse XDB -C18 (150 x 4.6 mm, 5 Âµ) column with an isocratic mobile phase of Methanol: Water (50: 50 v/v, pH of 3.0) at a flow rate of 0.8 mL/min. Protonated ions formed by a turbo ionspray in a positive mode was used to detect analyte and internal standard (IS). The MS/MS detection was made by monitoring the fragmentation of m/z 172.20â†’154.20 for Gabapentin and m/z 176.40â†’158.10 for internal standard on a mass spectrometer. Results: The method was validated over the concentration range of 51.356 ng/mL to 8217.008 ng/mL for Gabapentin in human plasma with correlation coefficient greater than 0.98. Conclusion: The developed method was successfully applied for analyzing Gabapentin in plasma samples for a bioequivalence study with healthy volunteers. Â Key words: Gabapentin; Validation; Analysis; Bioavailability; LC-MS/MS.